Structure-guided engineering of prototype foamy virus Env identifies key residues for heparan sulfate binding and enhances transduction efficiency - Shin, Hee-Seung; Cho, Soo-Yeon; Kwon, Yujin; Jung, Seong-Mook; Seo, Eun Sang; Son, Young Min; Kim, Eui Tae; Kim, Doyoun; Kim, Kyoung-Dong (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectivePrototype foamy virus (PFV) is an attractive gene delivery platform due to its large cargo capacity and favorable safety profile; however, the structural basis of its interaction with heparan sulfate (HS), a critical attachment factor for viral entry, remains undefined. The objective of this study was to identify the structural determinants of HS recognition within PFV Env and to evaluate whether rational, structure-guided engineering could enhance viral entry and gene transfer efficiency.MethodsWe applied a structure-guided engineering strategy combining in silico structural modeling, molecular docking, and systematic mutagenesis of the PFV Env receptor-binding domain (RBD), targeted residue substitutions, and combinatorial mutations spanning the upper domain (UD) and lower domain (LD) were generated and evaluated using quantitative cell-based transduction assays. In addition, Tet-On-inducible Env-expressing stable producer cell lines were established to provide a reproducible platform for functional validation.ResultsAlanine substitutions at R298, R440, and E446 in the UD abolished infectivity, confirming their essential roles in HS-mediated attachment. In contrast, selective substitutions at adjacent positions, Q296R and G403F in the UD, and E232N, I330F, and I334F in the LD, enhanced transduction efficiency by up to 1.32-fold relative to the wild type. Combinatorial variants integrating beneficial UD and LD mutations exhibited synergistic effects, achieving a transduction efficiency of 68.9%, corresponding to a 1.55-fold increase over the wild type (44.4%). Interspecies domain replacement with simian foamy virus Env reduced infectivity, underscoring the context-specific nature of PFV-HS interactions. In the inducible stable cell system, the LD var6 mutant achieved 8.6% transduction compared to 4.4% for the wild type, representing up to a 1.95-fold increase.DiscussionThese findings define the structural determinants of HS recognition in PFV Env and demonstrate that residue-level, structure-guided engineering can enhance PFV transduction efficiency. This study provides experimentally validated insight into PFV Env-HS interactions and establishes a rational framework for further optimization of PFV-based gene delivery technologies.